Dampak Penggunaan Smartphone terhadap Perkembangan Kognitif Anak Usia Dini - Khoirun Nisa Zein Lubis; Muhammad Amsal Nasution; Mhd Daud Batubara; Cindy Rohaya Nasution; Nadia Aslan Koto (Getpress Management Journals, 2025)
The development of digital technology has had a significant impact on children’s cognitive development. This study aims to analyze the knowledge, attitudes, and effects of gadget use on early childhood development in Paranbatu Village, as well as to formulate effective socialization strategies for the community. The research employed a qualitative descriptive approach through interviews, observations, and documentation involving parents, early childhood education (PAUD) teachers, and community leaders. The findings show that most parents have insufficient digital literacy; 60% use gadgets primarily for entertainment, 30% as learning tools, and 10% do not understand how to control content or manage children’s screen time. The positive impacts of gadget use include improved cognitive skills and creativity, while the negative effects involve reduced social interaction, the emergence of aggressive behavior, and decreased physical activity. These findings reinforce the importance of parental supervision supported by educational, religious, and community-based approaches to foster digital awareness and guide children in using technology wisely.